1984
DOI: 10.1093/nar/12.10.4247
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Z form poly(dG-dC). poly(dG-dC) with divalent metal ions: localization of the binding sites by I.R. spectroscopy

Abstract: Interacdon of Z form poly (dG-dC ABSTRACTThe secondary structures of poly(dG-dC).poly(dG-dC) in the presence of alcaline, alcaline earth and first row transition metal ions (Na+, Mg2+, Co2+, Ni2+) are investigated by infrared spectroscopy. The conformational transitions are studied as a function of the hydration of the polynucleotide and counter-ion nature and content. The use of selectively deuterated poly(dG-dC).poly(dG-dC) on the 8-carbon of guanines allows to show that a direct interaction occurs between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…In contrast, when poly(dA-dT) (which has no intercalation sites available for cationic porphyrins) is complexed with BAP or H 2 TMPyP-4, no appreciable change is detected in the spectral region of the double bond stretching vibrations of the adenines and thymines (data not shown). Figures 8e and h. Earlier studies, which bore on poly(dG-dC), revealed by C 8 -H selective deuteration that the broad band at 1498 cm -1 is a superposition of both cytosine and guanine absorption bands (94), and that the guanine component stems from the N 7 -C 8 -H deformation (95,96). Modifications of the position or of the relative intensity of this band could therefore be used as a diagnostic for interactions involving N 7 of guanine.…”
Section: Circular Dichroismmentioning
confidence: 76%
“…In contrast, when poly(dA-dT) (which has no intercalation sites available for cationic porphyrins) is complexed with BAP or H 2 TMPyP-4, no appreciable change is detected in the spectral region of the double bond stretching vibrations of the adenines and thymines (data not shown). Figures 8e and h. Earlier studies, which bore on poly(dG-dC), revealed by C 8 -H selective deuteration that the broad band at 1498 cm -1 is a superposition of both cytosine and guanine absorption bands (94), and that the guanine component stems from the N 7 -C 8 -H deformation (95,96). Modifications of the position or of the relative intensity of this band could therefore be used as a diagnostic for interactions involving N 7 of guanine.…”
Section: Circular Dichroismmentioning
confidence: 76%
“…A and B geometries and the B -, A conformational transition of DNA, alone or in the presence of polypeptides, proteins, or drugs, in highly concentrated conditions (hydrated films), have been characterized and followed by this technique (10)(11)(12). The left-handed Z structure of poly(dG-dC).poly(dG-dC) has also been investigated by ir spectroscopy (13)(14)(15)(16)(17), and we have previously shown that, in films, the reversible B -, Z transition can be induced by varying the relative humidity (18). This conforrnational transition has been identified by correlating the ir and uv absorbance spectroscopy results obtained on the same films, in the same salt and hydration conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2b). [88][89][90][91] The left-handed sequences have been found in natural DNA and are believed to play a major role in many fundamental life processes, including gene regulation and DNA replication. 92,93 One of the first spectroscopic techniques used for investigations of DNA B-Z transition was ECD.…”
Section: Illustrative Examples Dna B-z Transitionmentioning
confidence: 99%